2023
DOI: 10.3390/molecules28227540
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anti-Inflammatory Mechanism of β-Carotene Based on Network Pharmacology

Shilin Wu,
Ran Chen,
Jingyun Chen
et al.

Abstract: β-carotene is known to have pharmacological effects such as anti-inflammatory, antioxidant, and anti-tumor properties. However, its main mechanism and related signaling pathways in the treatment of inflammation are still unclear. In this study, component target prediction was performed by using literature retrieval and the SwissTargetPrediction database. Disease targets were collected from various databases, including DisGeNET, OMIM, Drug Bank, and GeneCards. A protein–protein interaction (PPI) network was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…100 Based on the structural and efficacy similarities between drugs, network pharmacology applies systems biology technology and database resources to analyze target molecules, construct related networks, predict drug targets and guide new drug discovery. Wu et al applied network pharmacology to identify potential core targets and possible signal pathways of the anti-inflammatory effects of β-carotene, including IL-6, 101 but did not perform experimental validation. Guo et al also found that TNF-α, IL-6 and IL-1β were the core target proteins of Er Miao San (EMS) for the treatment of inflammation, and suggested that EMS mainly exerted its anti-inflammatory effects by inhibiting the multiple pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…100 Based on the structural and efficacy similarities between drugs, network pharmacology applies systems biology technology and database resources to analyze target molecules, construct related networks, predict drug targets and guide new drug discovery. Wu et al applied network pharmacology to identify potential core targets and possible signal pathways of the anti-inflammatory effects of β-carotene, including IL-6, 101 but did not perform experimental validation. Guo et al also found that TNF-α, IL-6 and IL-1β were the core target proteins of Er Miao San (EMS) for the treatment of inflammation, and suggested that EMS mainly exerted its anti-inflammatory effects by inhibiting the multiple pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%